2017
DOI: 10.1038/s41598-017-11205-0
|View full text |Cite
|
Sign up to set email alerts
|

Responses of plant species diversity and soil physical-chemical-microbial properties to Phragmites australis invasion along a density gradient

Abstract: The invasion of ecosystems by strongly colonising plants such as Phragmites australis is viewed as one of the greatest threats to plant diversity and soil properties. This study compared a range of diversity measures including soil properties and mycorrhizal potential under different degrees of Phragmites density among three populations in coastal wetland, Victoria, Australia. Species richness, evenness and Shanon-Wiener index had significantly higher values in low degree of Phragmites density in all populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…Eight stems, each consisting of 14 14-19 cm long green leaves, were attached to each board, providing a stem density of 160 per m 2 . This stem density is in line with high density areas of Phragmites (Uddin & Robinson, 2017), an emergent macrophyte found in Tanzanian freshwater systems. Identical shelters were also placed in each of the housing tanks to remove novelty and to encourage individuals to associate the structure with shelter.…”
Section: Methodssupporting
confidence: 84%
“…Eight stems, each consisting of 14 14-19 cm long green leaves, were attached to each board, providing a stem density of 160 per m 2 . This stem density is in line with high density areas of Phragmites (Uddin & Robinson, 2017), an emergent macrophyte found in Tanzanian freshwater systems. Identical shelters were also placed in each of the housing tanks to remove novelty and to encourage individuals to associate the structure with shelter.…”
Section: Methodssupporting
confidence: 84%
“…ex Steudel) is a clonal perennial plant that grows in a wide variety of ecosystems, including swamp, coastal marshes, inland lakes, and rivers [ 28 , 29 ]. It has high adaptability, and a well-developed aerenchym and rhizosphere to facilitate colonization, and readily propagates by rhizome or stem node [ 30 , 31 ] It has a well-developed aerated tissue [ 32 ]. Previous studies have showed that P .…”
Section: Methodsmentioning
confidence: 99%
“…Most species of the genus Melaleuca are reliant on seed alone for reproduction; however, Melaleuca can form clonal stands through the production of ramets 69 . These two species naturally coexist in most of the wetlands in south-eastern Australia 70,71 .…”
Section: Methodsmentioning
confidence: 99%
“…Net nitrification was calculated as extractable nitrate in the incubated sample minus extractable nitrate in the initial extracts. Microbial biomass nitrogen (MBN) and dehydrogenase activity (DHA) in treated soil were determined according to the procedures of Uddin & Robinson 71 . The alkaline persulfate oxidation method was used to determine the total nitrogen in above-ground plant tissue of the above greenhouse experimental samples of both species following the method proposed by Purcell & King 76 .…”
Section: Laboratory Analysismentioning
confidence: 99%